PEMANFAATAN DIGITAL UNTUK MENINGKATKAN PENDAPATAN USAHA RUMAHAN PADA MASA PANDEMI COVID 19 - Irmah Halimah Bachtiar; Nursyam Ar; Ardiansyah Ali; Ibadurrahman; Abdul Hafid (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2021)
The COVID-19 pandemic has had a huge impact on human life all over the world.This disaster affects not only large cities, but also small towns and villages.Almost every aspect of life, including the household, undergoes significant changes.The community, particularly home-based business actors, will benefit greatly from digital acceleration in the business sector.Innovative individuals can emerge to build creative businesses by combining the internet and smartphones. As is well known, internet services can be accessed from anywhere, making it simple for anyone to connect with one another via smartphone. Business actors must take advantage of this opportunity to digitally develop their businesses. This community service activity will be carried out through counseling, which will include material presentation and discussion with PKM participants.The activity's conclusion is that there is more knowledge about how to use digital as a home business to supplement income during the COVID-19 pandemic, as well as the benefits in the context of community empowerment in Beroanging Village.